Dialkylation of Diethyl Ethoxycarbonylmethylphosphonate under Microwave and Solventless Conditions. Issue 2 (4th March 2014) - Grün, Alajos; Blastik, Zsófia; Drahos, László; Keglevich, György
ABSTRACT To further broaden the methods for the heterogeneous phase alkylation of CH acidic compounds, the dialkylation of diethyl ethoxycarbonylmethylphosphonate was studied in the presence of Cs2CO3 under microwave and solvent‐free conditions. It was found that after repeating the alkylations by the addition of newer portions of the alkylating agent and the base on a few occasions, the dialkylation was quite efficient. Even dialkyl derivatives with different alkyl groups could be synthesized. The presence of a phase‐transfer catalyst was harmful, as prevented the formation of the dialkyl products.